2007
DOI: 10.1103/physrevb.75.161102
|View full text |Cite
|
Sign up to set email alerts
|

Coherent vibrations of submicron spherical gold shells in a photonic crystal

Abstract: Coherent acoustic radial oscillations of thin spherical gold shells of submicron diameter excited by an ultrashort optical pulse are observed in the form of pronounced modulations of the transient reflectivity on a subnanosecond time scale. Strong acousto-optical coupling in a photonic crystal enhances the modulation of the transient reflectivity up to 4%. The frequency of these oscillations is demonstrated to be in good agreement with Lamb theory of free gold shells.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
34
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 23 publications
0
34
1
Order By: Relevance
“…Recently, Mazurenko et al reported vibrational beats in silica-core gold-shell particles assembled in a 3D photonic crystal, where they found the peakto-peak amplitude reached 4 % of the total reflectivity and the dephasing time was (0.6 ± 0.2) ns. [27] Their modulation amplitude is two times higher than ours, which could be due to the thicker photonic crystal, and thus stronger acousto-optical coupling. Their modulation dephasing time is much shorter than ours, which could be attributed to the larger size distribution of their particles than ours.…”
mentioning
confidence: 92%
“…Recently, Mazurenko et al reported vibrational beats in silica-core gold-shell particles assembled in a 3D photonic crystal, where they found the peakto-peak amplitude reached 4 % of the total reflectivity and the dephasing time was (0.6 ± 0.2) ns. [27] Their modulation amplitude is two times higher than ours, which could be due to the thicker photonic crystal, and thus stronger acousto-optical coupling. Their modulation dephasing time is much shorter than ours, which could be attributed to the larger size distribution of their particles than ours.…”
mentioning
confidence: 92%
“…1 Colloidal crystals, formed by self-assembly of polystyrene and silica nanospheres have shown phononic band gaps in the gigahertz frequency range, [2][3][4][5][6][7] which corresponds to a picosecond timescale. From that respect, probing ultrafast dynamics in colloidal crystals has attracted interest in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…There are a few techniques that measure vibrations excited by light waves in nanosized colloidal crystals, such as Brillouin light scattering, 2,5 Raman scattering, 8 and optical pump-probe spectroscopy. 4,6,7 However, optical techniques can only be applied to the structures with period comparable to the wavelength of light and are severely limited in terms of the accessible spatial resolution, due to restriction on the highest Fourier components. Moreover, sufficient refractive index matching is often very difficult, if not impossible.…”
Section: Introductionmentioning
confidence: 99%
“…This interest is due to various potential applications in acousto-optical devices which can be used for ultrafast manipulation and control of electromagnetic waves by hypersonic (GHz) acoustic waves [1]. Colloidal crystals, formed by the self-assembly method, have shown phononic band gaps in the GHz frequency range [2][3][4][5][6][7]. Due to the recent progress in the fabrication of high-quality colloids, this provides an opportunity to produce inexpensive phononic crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamics in submicrometer colloidal crystals was investigated using different techniques such as Raman scattering [8], Brillouin light scattering [2], and optical pump-probe spectroscopy [4][5][6][7]. However, these methods have limited spatial resolution and are not suitable for the observation of the detailed structure of the sample.…”
Section: Introductionmentioning
confidence: 99%